Powstawanie wad wrodzonych tarczy nerwu wzrokowego. Część II. Wady wrodzone tarczy nerwu wzrokowego z nieprawidłową wielkością tarczy - Wojtulewicz, Małgorzata; Marcinkiewicz, Władysław; Stankiewicz, Andrzej; Rękas, Marek; Kosatka, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Embryological conditions, each of fifth congenital anomalies of the optic disc from the group of anomalies of inappropriate optic diameter was described. Few available epidemiological data were given. The influence of medications, drugs, intoxications, as well as premature birth on genesis of congenital anomalies was taken into consideration. Malformation of central nervous system was introduced together with clinical syndromes related to congenital anomalies of the optic disc indicating the genetic condition.